Dystonia and Infantile Glutaric Acidemia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
Glutaric acidemia, an autosomal recessively inherited disease caused by deficiency of glutaryl-CoA dehydrogenase, was manifested by acute dystonia in 3 infants reported from the Children's Hospital of Pittsburgh, Pennsylvania.